Persuasive Technology : 14th International Conference, PERSUASIVE 2019 Limassol, Cyprus, April 9–11, 2019 Adjunct Proceedings - Kyza, Eleni A.; Karppinen, Pasi; Karapanos, Evangelos; Win, Khin Than; Oinas-Kukkonen, Harri (My University, 2019)
Persuasive technology is a vibrant interdisciplinary research field, focusing on the study, design, development, and evaluation of information technologies aimed at influencing people’s attitudes or behaviors through open and transparent means. The International Conference on Persuasive Technology series brings together researchers, designers, practitioners and business people from various disciplines and a wide variety of application domains. The research community seeks to facilitate healthier lifestyles, make people feel or behave more safely, reduce consumption of renewable resources, among other notable goals, by, for instance, designing software applications, monitoring through sensor technologies, analyzing obtained data, and providing various types of coaching for users. The 14th International Conference on Persuasive Technology was hosted by the Department of Communication and Internet Studies at the Cyprus University of Technology in Limassol, Cyprus in April 2019, and organized in collaboration with the University of Oulu, Finland and the University of Wollongong, Australia. In previous years similar highly successful conferences were organized in Waterloo (Canada), Amsterdam (Netherlands), Salzburg (Austria), Chicago (United States), Padua (Italy), Sydney (Australia), Linköping (Sweden), Columbus (United States), Copenhagen (Denmark), Claremont (United States), Oulu (Finland), Palo Alto (United States), and Eindhoven (Netherlands). The conference addressed a wide variety of topics regarding the development of persuasive and behavior change support systems. This year papers were also solicited for two specific topics, namely Personal informatics and Gamification and gamified persuasive technologies.
Keywords: Persuasive technology; Information technologies